(untitled) (Clinics, 2020)
OBJECTIVES: This study aimed to analyze the efficiency of physiotherapy techniques in sputum induction and in the evaluation of pulmonary inflammation in asthmatic children and adolescents. Although hypertonic saline (HS) is widely used for sputum induction (SI), specific techniques and maneuvers of physiotherapy (P) may facilitate the collection of mucus in some asthmatic children and adolescents. METHODS: A randomized crossover study was performed in patients with well-controlled asthma, and 90 sputum samples were collected. Children and adolescents were assessed using spirometry and randomized at entry into one of three sputum induction techniques: (i) 3% hypertonic saline – HS technique; (ii) physiotherapy (oscillatory positive expiratory pressure, forced expiration, and acceleration of expiratory flow) – P technique; and (iii) hypertonic saline + physiotherapy – HSP technique. ClinicalTrials.gov: NCT03136042. RESULTS: The total cells (mL) and the percentage (%) of differential inflammatory cells were similar in all techniques. The sputum weight (g) in the HSP technique was significantly higher than that in the HS technique. In all techniques, the percentage of viable cells was 450%, and there was no difference between the HS and P techniques. Moreover, sputum induction did not cause any alterations in the pulmonary function of patients. CONCLUSION: The physiotherapy sputum collection technique was effective in obtaining viable cells from mucus samples and yielded the same amount of sputum as the gold standard technique (hypertonic saline). In addition, the physiotherapy maneuvers were both safe and useful for sputum induction in asthmatic children and adolescents with well-controlled asthma.